Cardiac Pacing and Defibrillation in Children and Young Adults - Singh, Harinder R (Indian Heart Rhythm Society, 2013)
The population of children and young adults requiring a cardiac pacing device has been consistently increasing. The current generation of devices are small with a longer battery life, programming capabilities that can cater to the demands of the young patients and ability to treat brady and tachyarrhythmias as well as heart failure. This has increased the scope and clinical indications of using these devices. As patients with congenital heart disease (CHD) comprise majority of these patients requiring devices, the knowledge of indications, pacing leads and devices, anatomical variations and the technical skills required are different than that required in the adult population. In this review we attempt to discuss these specific points in detail to improve the understanding of cardiac pacing in children and young adults.